2010
DOI: 10.1002/mds.23194
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile levodopa‐responsive Parkinsonism with early orobuccolingual dyskinesias and cognitive impairment

Abstract: A 13-year old girl presented with slowly progressive rest tremor of the hands, bradykinesia, and rigidity. The symptoms improved with dopaminergic medications, but severe drug-induced dyskinesias developed early. She subsequently developed cognitive slowing and difficulty initiating saccadic eye movements. She went on to have deep brain stimulation surgery. Experts discuss the syndromal diagnosis and predict the underlying pathology. The pathological diagnosis is given and clinical learning points are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, Sone et al reported the usefulness of skin biopsy for diagnosing NIID in 2011 [4], after which a wide range of clinical manifestations have been demonstrated in patients with adult-onset NIID including cognitive impairment, pyramidal and extrapyramidal symptoms, cerebellar ataxia, neuropathy, and autonomic dysfunction [4], [5]. With regard to epilepsy, seizure-like episodes such as recurrent syncope or falls have only been reported in six adults with NIID, although children with this disease often have seizures [1], [2], [3], [11], [12], [13]. Espay et al reported a 20-year-old woman with recurrent episodes of momentary loss of consciousness accompanied by mood changes, in whom EEG also demonstrated generalized periodic discharges [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Sone et al reported the usefulness of skin biopsy for diagnosing NIID in 2011 [4], after which a wide range of clinical manifestations have been demonstrated in patients with adult-onset NIID including cognitive impairment, pyramidal and extrapyramidal symptoms, cerebellar ataxia, neuropathy, and autonomic dysfunction [4], [5]. With regard to epilepsy, seizure-like episodes such as recurrent syncope or falls have only been reported in six adults with NIID, although children with this disease often have seizures [1], [2], [3], [11], [12], [13]. Espay et al reported a 20-year-old woman with recurrent episodes of momentary loss of consciousness accompanied by mood changes, in whom EEG also demonstrated generalized periodic discharges [3].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to epilepsy, seizure-like episodes such as recurrent syncope or falls have only been reported in six adults with NIID, although children with this disease often have seizures [1], [2], [3], [11], [12], [13]. Espay et al reported a 20-year-old woman with recurrent episodes of momentary loss of consciousness accompanied by mood changes, in whom EEG also demonstrated generalized periodic discharges [3]. In addition, Toyota et al reported a 70-year-old woman with recurrent falls, in whom EEG revealed mid-temporal spikes and sharp waves [13], but there were no features of NCSE associated with GPDs like our case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations